Sex‐specific associations of cardiorespiratory fitness and galectin‐3 in the general population - Magdalena E. Haid; Stephanie Zylla; Marcello Ricardo Paulista Markus; Nele Friedrich; Ralf Ewert; Sven Gläser; Stephan B. Felix; Marcus Dörr; Martin Bahls (ESC Heart Failure, 2022)
Abstract Aims Low cardiorespiratory fitness (CRF) is associated with greater mortality and morbidity. Galectin‐3 (Gal‐3) is a prognostic biomarker for fibrosis and heart failure. Gal‐3 is also associated with a greater risk for cardiovascular mortality. Whether CRF is related with Gal‐3 is unclear. The objective of this study was to assess the sex‐specific associations of CRF and Gal‐3 levels in the general population. Methods Gal‐3 concentrations were determined using a sandwich enzyme immunoassay in the population‐based Study of Health in Pomerania (SHIP‐TREND‐0). Sex‐stratified linear regression models adjusted for age, current smoking status, and renal function were used. Individuals with left ventricular ejection fraction (LVEF) <40%, previous myocardial infarction, atrial fibrillation, chronic lung disease, severe renal disease (estimated glomerular filtration rate <30 mL/min/mm2), a history of cancer, and extreme values for Gal‐3 (<1st percentile; >99th percentile) were excluded. Results A total of n = 1515 participants with a median age of 49 (IQR: 39–60 years, 48% males) were included. In men, a 1 L/min greater VO2peak was significantly related to 0.50 ng/mL (95% CI −0.8068 to −0.1938, P < 0.01) less Gal‐3. In males, a 1 mL/min/kg higher VO2peak adjusted for body weight was associated with −0.0286 ng/mL (95% CI −0.0052 to −0.0005, P = 0.02) less Gal‐3. When VO2peak was adjusted for lean mass 1 mL/kg/min more was correlated with a −0.0022 ng/mL (95% CI −0.0043 to ‐0.0007, P = 0.04) less Gal‐3. In women, VO2peak (β −0.2046 95% CI −0.6541 to 0.2449, P = 0.37) and VO2peak adjusted for lean mass (β −0.0019 95% CI −0.0421 to –0.0050, P = 0.12) were not related with Gal‐3, whereas a 1 mL/min/kg higher VO2peak adjusted for body weight was significantly associated with a −0.0064 ng/mL lower Gal‐3 (95% CI −0.0092 to ‐0.0035, P < 0.01). There were no differences between pre‐menopausal and post‐menopausal women. Conclusions VO2peak was associated with Gal‐3 only in men, but VO2peak adjusted for body weight in women and men. Our results suggest that the adverse consequences of low CRF may be mediated by Gal‐3. Further research is needed to understand the sex‐specific association between CRF and Gal‐3 and whether they are clinically relevant.